Molecular phylogeny of Cousinia sections Albidae, Stenocephalae and Cousinia (Asteraceae): Systematic implications - Kalouti, Simin; Kazempour Osaloo, Shahrokh; Attar, Farideh; Susanna, Alfonso; Garcia-Jacas, Núria (Phytotaxa, 2022)
Cousinia sect. Stenocephalae is a mainly Iranian section of the genus and the second largest section of Cousinia after C. sect. Cynaroidae. Its members are mainly distributed in Iran. Using nrDNA ITS sequences, together with morphological evidence where possible, we tested the monophyly of C. sect. Stenocephalae as well as the related C. sect. Albidae and C. sect. Cousinia. We reconstructed phylogenetic relationships within these sections by performing a Bayesian analysis on a sample of 153 species of Cousinia, of which 49 species belong to the study sections. The analysis revealed that C. sect. Stenocephalae, Albidae and Cousinia are not monophyletic, which lays stress upon the need of a deep reexamination of the sectional classification in Cousinia using a different approach.